“ETAIKEN WEREK”: HATI MENURUT ORANG HUWULA - Meki Mulait (Studi Budaya Nusantara, 2017)
AbstractThe role of the heart is very important in human life. The heart is not only synonymous with feeling but also has a rational intuitive. With careful human life develops in a balanced and meaningful. Thereby heart being one of the central human strength that should be put forward. Forward the heart does not mean ignoring other powers such as seeing, feeling, thinking, and acting up to the soul and spirit in relation to the Supreme Being. Putting forward the 'heart' means "heart is central" (central) in all human activities done with various abilities that exist in him. In this reflection I will show that the heart must be a shaft for all human strength. The location of the heart at the central point can connect the whole reality of human power to enable man to lead to the wisdom of his life. Humans who only rely on the ratio is not necessarily wise or who just rely on feelings are also not necessarily wise. Similarly a diligent man, not necessarily wise. Man is said to be wise when all elements of humanity function in a balanced way. It is the heart that unites all the elements of humanity.